2011
DOI: 10.1186/1471-2490-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction among married couples living in Kumasi metropolis, Ghana

Abstract: BackgroundSexuality and its manifestation constitute some of the most complex of human behaviour and its disorders are encountered in community. Sexual dysfunction is more prevalent in women than in men. While studies examining sexual dysfunction among males and females in Ghana exist, there are no studies relating sexual problems in males and females as dyadic units. This study therefore investigated the prevalence and type of sexual disorders among married couples.MethodThe study participants consisted of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
3
31
1
2
Order By: Relevance
“…9 Communication problems have been underlined as a common complaint presented by couples seeking marital therapy. 29,31 It was determined in one study in Turkey that family education program was effective in increasing marital adjustment and state of emotional reactiveness in the family system; however, it was ineffective in problem solving, communication, roles, affective involvement, behavior control and general function. 32 In conclusion, experience of sexual problems during pregnancy increased the risk of negative effects on marital harmony within the couples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Communication problems have been underlined as a common complaint presented by couples seeking marital therapy. 29,31 It was determined in one study in Turkey that family education program was effective in increasing marital adjustment and state of emotional reactiveness in the family system; however, it was ineffective in problem solving, communication, roles, affective involvement, behavior control and general function. 32 In conclusion, experience of sexual problems during pregnancy increased the risk of negative effects on marital harmony within the couples.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies concluded that vaginismus prevalence was 68.1 and 69.3% of non-pregnant women in Ghana. 16,29 Association between characteristics of women and sexuality during pregnancy Sexual satisfaction is an integral part of life and human wellbeing. In the study, total GRISS score was found higher in women with lower educational level, living with three or more people in home, being multiparious, unplanned pregnancy, having pain during sexual intercourse and women who reported their sexual life were very affected during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It may be supported by the theory that with an increase in duration of marriage, there is a decrease in frequency of intercourse leading to satisfaction disorder. [10]…”
Section: Discussionmentioning
confidence: 99%
“…FSD was present in 47.6% of females with duration of marriage >20 years. It may be supported by theory that with increase in duration of marriage, there is decrease in frequency of intercourse leading to satisfaction disorder (18) . Physically inactive or females in sedentary life style suffer more from FSD (44.4%) than physically active women (20%).…”
Section: Discussionmentioning
confidence: 52%